The complete mitochondrial genome of Capricornis sp., possible a new species of Serow from Guizhou, China. (3rd March 2016) - Dou, Hailong; Zhang, Li; Li, Chongqing; Mu, Jun; Wang, Tianming; Ge, Jianping; Feng, Limin
Abstract: The genus Capricornis was widely distributed in Asia. In the present study, the complete mitochondrial genome of Capricornis sp., possible a new species of Serow from Guizhou province of China, was sequenced for the first time. Sequence analysis showed it is 16, 441 bp in length, consisting of 12S rRNA gene, 16S rRNA gene, 22 transfer RNA (tRNA) genes, 13 protein-coding genes and one control region (CR).